Mathematical modeling and control of active suspension system for a quarter car railway vehicle - Ahmed, M. I; Md Yusof, Hazlina; Rashid, M. M (Institute Mathematical Sciences, Universiti Putra Malaysia, 2016)

(untitled)
Active suspension is a term where active components are incorporated in a mechanical suspension system. Compared to passive suspension, the active suspension provides improved feature of suspension in terms of ride quality and vehicle handling. While the passive suspension consists of spring and dampers, the active suspension comprises of sensors, actuators and controller with passive system. The actuator in the active suspension provides forces to the suspension which eventually improves ride performance and comfort.This paper presents the early stage of modeling an active suspension of a railway vehicle. The mathematical model of the system is demonstrated and the early suspension control of the vehicle is introduced. As a start only the quarter car vehicle is considered and tested upon random or irregular track input at a speed of 31 m/s. The skyhook control strategy is introduced to the suspension, making it an active system. The performance is then compared to the passive. Preliminary results have shown that the active suspension improves ride quality by reducing the vehicle body accelerations and suspension deflections.